Fear of entrepreneurship among university graduates: a psychological analysis (2012)
Despite entrepreneurship being an attractive alternative to youth unemployment, university many university graduates are reluctant to embark on it as a career, even when the opportunity exists. This may be because of psychological factors that inhibit or even prevent entrepreneurship being considered as a desirable or even a viable career option. The present study examines the role of psychological factors, especially fear of failure as an entrepreneur, among university graduates, in this case in Nigeria. A specially-developed questionnaire was completed by 1100 university graduates (729 males and 371 females) with a mean age of 32 years. Findings confirmed core self evaluation as influencing fear of entrepreneurship. Also, pre-entrepreneurial intention, attitude, and capacity significantly predicted fear of entrepreneurship. The fact that these psychological variables affect the intention to become an entrepreneur, suggests that they need to be considered in the selection placement, and training of university graduates for entrepreneurship,' It is also because these variables play an important role in innovation, creativity, and adjustment to changes which are as inevitable in management as they are in entrepreneurship. Future studies need to cover more psychological variables and different samples